Research and experience (2011)
Based on personal research experience, the author of the article reflects on the relationship between research and experience, with the intention of helping to extend the reflection to both researchers and those who are starting in the research field. The conditions for moving between research and experience, are given by explaining the relationship between one and the other, as well as the role of the researcher in this process.